Why are western diet and western lifestyle pro-inflammatory risk factors of celiac disease? - Skoracka, Kinga; Hryhorowicz, Szymon; Rychter, Anna Maria; Ratajczak, Alicja Ewa; Szymczak-Tomczak, Aleksandra; Zawada, Agnieszka; Słomski, Ryszard; Dobrowolska, Agnieszka; Krela-Kaźmierczak, Iwona (Frontiers in Nutrition, 2023)
The prevalence of celiac disease increased in recent years. In addition to the genetic and immunological factors, it appears that environmental determinants are also involved in the pathophysiology of celiac disease. Viral infections may contribute to the development of celiac disease. Current research does not directly confirm the protective effect of natural childbirth and breastfeeding on celiac disease. However, it seems that in genetically predisposed children, the amount of gluten introduced into the diet may have an impact on celiac disease development. Also western lifestyle, including western dietary patterns high in fat, sugar, and gliadin, potentially may increase the risk of celiac disease due to changes in intestinal microbiota, intestinal permeability, or mucosal inflammation. Further research is needed to expand the knowledge of the relationship between environmental factors and the development of celiac disease to define evidence-based preventive interventions against the development of celiac disease. The manuscript summarizes current knowledge on factors predisposing to the development of celiac disease including factors associated with the western lifestyle.